The association between non-standard employment, job insecurity and health among British adults with and without intellectual impairments: Cohort study - Eric Emerson; Chris Hatton; Janet Robertson; Susannah Baines (Elsevier, 2018)
We sought to investigate the association between employment conditions and health among working age British adults with and without intellectual impairments. Using data from the 1970 British Cohort Study, we undertook a series of cross sectional analyses of the association between employment conditions and health (self-reported general health, mental health) among British adults with and without intellectual impairments at ages 30, 34 and 42. Our results indicated that: (1) British adults with intellectual impairments were more likely than their peers to be exposed to non-standard employment conditions and experience job insecurity; (2) in both groups exposure was typically associated with poorer health; (3) British adults with intellectual impairments in non-standard employment conditions were more likely than their peers to transition to economic inactivity; (4) among both groups, transitioning into employment was associated with positive health status and transitioning out of employment was associated with poorer health status. British adults with intellectual impairments are significantly more likely than their peers to be exposed to non-standard and more precarious working conditions. The association between employment conditions and health was similar for British adults with and without intellectual impairments. As such, the study found no evidence to suggest that research on causal pathways between employment and health derived from studies of the general population should not generalize to the population of people with intellectual impairments. Keywords: Employment conditions, Non-standard employment, Precarious employment, Health, Intellectual disability, Intellectual impairment, Borderline intellectual functioning, Cognitive ability